Assessment of water quality and solid waste management in Hinulugang Taktak, Antipolo City - De Leon, Jodie Danielle P.; Fabulare, Ariane D.
Hinulugang Taktak National Park is one of the most visited tourist attractions in Antipolo City for scenic and recreation purposes. However, the park, especially the Hinulugang Taktak Waterfalls, was heavily polluted which lead to its closing and rehabilitation in October 2012. This research aims to identify the sources of waste and water pollution of the park and assess the current water quality of the waterfalls, alongside with the assessment of the creek waters flowing into the falls. This study also aims to assess the current solid waste management in and around Hinulugang Taktak. Assessment ofthe water quality shows that Hinulugang Taktak Waterfalls does not pass DAO 34 water quality standards for Class C Waters. Also, results show that the foam present and foul smell evident in the waterfalls are mainly due to the gray water coming from the residents living near the creek system of Hinulugang Taktak. Solid wastes are very minimal in the waterfalls, which was the effect of building trash traps at key points leading to the waterfalls. Solid waste management in Antipolo City complies with RA 9003, However, there is still a need for waste reduction especially those which flows into the creek system due to improper behavior of the residents.